Kecemasan Pandemi COVID-19 dengan Produksi dan Kelancaran Pengeluaran ASI Ibu Post Partum - Yusnidaryani Yusnidaryani; Marlina Marlina; Ainil Yusra; M. Jamil Fauzi (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the relationship between anxiety during the COVID-19 pandemic with the production, expenditure, and smoothness of postpartum mothers' breast milk at the Syamtalira Aron Health Center. The research method is an analytic survey using a cross-sectional design. The results showed no significant relationship between the anxiety of the COVID-19 pandemic and postpartum mothers' milk production. Also, there is no significant relationship between pressure during the COVID-19 pandemic and the release of breast milk. However, there is a relationship between anxiety during the COVID-19 pandemic with breastfeeding for mothers in the working area of the Syamtalira Aron Health Center. In conclusion, pressure during the COVID-19 pandemic can impact the smooth breastfeeding of postpartum mothers in the working area of the Syamtalira Aron Health Center. Keywords: Breastfeeding, Anxiety, COVID-19 Pandemic, Post Partum